TIPOLOGI PAHAM KEAGAMAAN MAHASISWA FAKULTAS ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI MAKASSAR - Amri Rahman, (Inspiratif Pendidikan, 2023)
This study aims to determine the typology of religious understanding of FIK UNM students through the model of religious studies followed by students of FIK UNM and their views on religious issues . The type of research used in this research is qualitative research using a descriptive approach. This research used purposive random sampling technique), namely the technique of determining the sample with certain considerations, then randomized, so that the samples in this study were active and inactive students in religious study groups at the Faculty of Sports Science. The data collection technique conducted in this research is observation, interviews and documentation with the data analysis technique used is descriptive qualitative data analysis techniques. The results showed that the typology of religious understanding of FIK UNM students in general can be classified into 3 (three) types, namely inclusive, exclusive and moderate, but generally students have moderate religious understanding. The religious moderation of FIK UNM students can also be seen from their views on religious issues debated by ulama. FIK UNM students are welcome to differences of opinion, so they do not have a fanatical attitude towards one opinion nor do they blame other opinions.